Vikings. Season 5, volume 1 [videorecording (Blu-Ray)] - Hirst, Michael, 1952- (MGM, 2018)
Season Five begins with Ivar the Boneless asserting his leadership over the Great Heathen Army, while Lagertha reigns as Queen of Kattegat. Iver's murder of his brother Sigurd sets the stage for vicious battles to come, as Ragnar's sons plot their next move after avenging their father's death.